FEATURES OF REFORMING STATE FINANCIAL CONTROL IN THE REPUBLIC OF UZBEKISTAN - Suvankulov Aliaskar Rahmonkulovich (Journals Park Publishing, 2025)
The purpose of this article is to identify the main directions for improving the system of state financial control in the Republic of Uzbekistan. The principles for constructing a system of state financial control vary depending on the established historical, economic and legal traditions of the country. The article describes the current level of development of state financial control in the country and trends in the introduction of advanced international experience in order to increase the efficiency of financial control. It is known that standards of external state control are formed and approved by the national control and accounting authorities of the corresponding country, as a rule, taking into account the requirements of INTOSAI standards.
Keywords: Budget, control, budget control, financial control, state financial control, financial management system, supreme financial control bodies, internal financial control, internal audit, control bodies.